Simplify (x − 3)(x2 + 7x − 8). a x3 − 11x2 − 8x + 24 b x3 + 7x2 − 11x + 24 cx3 + 4x2 − 29x + 24 d x3 + 10x2 + 13x + 24

QUESTION POSTED AT 29/05/2020 - 01:12 AM

Answered by admin AT 29/05/2020 - 01:12 AM

(x - 3)(x^2 + 7x - 8) =
x(x^2 + 7x - 8) - 3(x^2 + 7x - 8) =
x^3 + 7x^2 - 8x - 3x^2 - 21x + 24 =
x^2 + 4x^2 - 29x + 24 <==
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

Graph the exponential function. y = 4(3) x

QUESTION POSTED AT 02/06/2020 - 01:30 AM

If f(x)=-5x-11. then f-(x)

QUESTION POSTED AT 02/06/2020 - 01:29 AM